Automatic detection of human parasite worm using microscopic image - Rushdina, Roslan (2012)
This project investigates about the development of automatic detection of egg of human parasites using microscopic images. The MATLAB software is the tool to analyse the image processing technique applied in this research. The stages of image processing technique are image acquisition, processing, classification and testing. The input image is a microscopic image with three different resolutions. The experiment parasites are found in faecal samples provided by doctor at HUSM. This project had been categorized the two types of parasites worm which is Roundworm, Ascaris Lumbricoides and Whipworm, Trichuris Trichiura. The identification of the parasites is based on its eggs roundness, shape and smoothness characteristics. The MATLAB software recognized the types of parasite based on classification that had been done before. The image processing used are edge detection, filling, morphological operation and others. The image of egg parasite will be expected to appear without other subjects inside result image. This project will give benefit to biomedical industry and human health as it acts as a specialist to acknowledge a patient’s condition by the existence of types of parasite living in one’s body.